Correlation Between Total Flavonoid Contents and Macrophage Phagocytosis Activity of Fractions From Faloak (Sterculia quadrifida R.Br.) Barks Ethanolic Extract In Vitro - Rima Munawaroh; Siswadi Siswadi; Erna Prawita Setyowati; Retno Murwanti; Triana Hertiani (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
On Timor island, Nusa Tenggara Timur, faloak barks (Sterculia quadrifida R.Br.) has been used empirically to restore stamina. Faloak bark ethanolic extract proved to have immunomodulatory activity in vitro, which can increase macrophage phagocytosis activity. This research aimed: (i) to determine the immunomodulatory active fraction of faloak bark ethanolic extract, (ii) to determine the total flavonoid contents of faloak extract and fractions, and (iii) to evaluate the correlation of the total flavonoid contents of those extract and fractions with their macrophage phagocytosis activity. The simplisia powder is macerated with 96% ethanol. The extract was dissolved in methanol:water (9:1v/v) was then subsequently partitioned with n-hexane, ethyl acetate, and water to obtain n-hexane fraction, ethyl acetate fraction, water fraction, and insoluble fraction. Faloak extract and fractions at concentration 62,5; 125; 250; 500μg/mL were tested for their effect on the peritoneal macrophage phagocytosis of Balb/c mice in vitro by the latex beads method. Phagocytosis capacity and phagocytosis index were analyzed using one-way anova and post hoc Tukey HSD test with 95% confidence level. The results showed that ethyl acetate fraction had the highest macrophage phagocytosis capacity and the highest total flavonoid content compared to other fractions. The highest macrophage phagocytosis capacity of ethyl acetate fraction at concentration of 250 μg/mL was 51,94±4,67%, this value was significantly different from cell control (7,50±1,29%), negative controls of 0,0625% dimethylsulphoxide (6,25±0,36%), as well as positive control of 200 μg/mL echinaceae extract syrup® (9,97±0,33%). The total flavonoid content of ethyl acetate fraction determined by aluminum chloride method was 4,290±0.029 mg of quercetin equivalent/g fraction. There was a positive and strong correlation between the total flavonoid content of these extract and fractions with their macrophage phagocytosis capacity (Pearson correlation coefficient of 0,781) and showing linear relationship y=4,721x+19,663; R2=0,61.